INVESTIGATION OF RELIGIOUS AND MORAL VALUES IN CHILDREN IN THE DIGITAL ERA - Dedek Nursiti Khodijah Nursiti Khodijah; Saptiani Saptiani; Nani Endri Santi; Mohamad Maulidin Alif Utama (STAI Asy-Syukriyyah, 2023)
The current technological advances in the digital world will of course be able to help parents and teachers instilling religious and moral values ​​in children. Therefore, the role of parents and teachers in instilling religious and moral values ​​in digital-based children is very urgent, so that digital use can be useful according to its function. The aim of this research is to describe how in the era of technology or digital attacks, parents have an important role in children's lives in instilling religious and moral values. This research is qualitative research with the Research Library research type. The results of this research are the use of digital tools and media as tools to help instill religious and moral values ​​in early childhood. Parents and teachers must be wise in directing, guiding and embracing their children to use media according to the function and purpose of digital media, so that children avoid excessive addiction and inappropriate media use.